2004
DOI: 10.1152/ajpendo.00366.2003
|View full text |Cite
|
Sign up to set email alerts
|

Age and aerobic exercise training effects on whole body and muscle protein metabolism

Abstract: .-Aging in humans is associated with loss of lean body mass, but the causes are incompletely defined. Lean tissue mass and function depend on continuous rebuilding of proteins. We tested the hypotheses that whole body and mixed muscle protein metabolism declines with age in men and women and that aerobic exercise training would partly reverse this decline. Seventy-eight healthy, previously untrained men and women aged 19-87 yr were studied before and after 4 mo of bicycle training (up to 45 min at 80% peak hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
320
3
13

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 397 publications
(353 citation statements)
references
References 49 publications
17
320
3
13
Order By: Relevance
“…The absence of an endurance training effect on muscle protein synthesis rates at rest, observed in the present study was in agreement with other results obtained in the tibialis anterior [39] and in the epitrochlearis [40] in rats. This conflicts with recent results in humans fed weight-maintaining diets reporting a stimulation at rest of muscle protein synthesis by endurance training [41,42]. The reason why protein fractional synthesis rates in the liver were lower at rest in trained rats than in sedentary rats remains unclear.…”
Section: Effect Of Endurance Trainingcontrasting
confidence: 63%
“…The absence of an endurance training effect on muscle protein synthesis rates at rest, observed in the present study was in agreement with other results obtained in the tibialis anterior [39] and in the epitrochlearis [40] in rats. This conflicts with recent results in humans fed weight-maintaining diets reporting a stimulation at rest of muscle protein synthesis by endurance training [41,42]. The reason why protein fractional synthesis rates in the liver were lower at rest in trained rats than in sedentary rats remains unclear.…”
Section: Effect Of Endurance Trainingcontrasting
confidence: 63%
“…Skeletal muscle mass usually contributes up to about 50 % of total body weight in young adults and decreases during ageing to approximately 25 % of total body weight by 75-80 years of age (Short et al 2004). For example, quadriceps muscle decreases by up to 40 % between the ages of 20 and 80 years (Lexell 1995).…”
Section: Lean Mass Decreasementioning
confidence: 99%
“…Although it was originally reported that healthy older adults had decreased rates of basal muscle protein synthesis (5,(25)(26)(27)(28)(29)(30)(31) , more recent studies have failed to reproduce these findings and generally show little or no differences in basal muscle protein synthesis rates between young and old adults (32)(33)(34)(35)(36)(37)(38)(39) . These discrepancies may be due to the standardisation of prior physical activity (24) , selection of subjects (30) or the selection of different precursor pools to calculate muscle protein synthesis (40) .…”
Section: Ageing and Protein Turnover In Skeletal Musclementioning
confidence: 99%
“…In addition, endurance (97,98,(104)(105)(106)(107)(108)(109)(110) exercise was shown to enhance the skeletal muscle oxidative capacity, resulting in greater endurance capacity (5,120) . Although the muscle regenerative capacity seems to decline at a more advanced age, the reduced satellite cell pool size (119) does not compromise the capacity for muscle hypertrophy to occur even at an advanced age (121)(122)(123) and resistance exercise training was shown to increase muscle fibre size (124)(125)(126)(127) .…”
Section: Long-term Interventionsmentioning
confidence: 99%